Changes in cytokine profiles following treatment with food allergen‐specific sublingual immunotherapy in dogs with adverse food reactions. Issue 6 (23rd July 2017) - Maina, Elisa; Devriendt, Bert; Cox, Eric
Abstract : Background: Food allergen‐specific sublingual immunotherapy (FA‐SLIT) is considered to be a novel, safe and effective approach in dogs with adverse food reactions (AFR). Hypothesis/Objectives: To investigate changes in key cytokines associated with FA‐SLIT. Animals: Eleven dogs with confirmed AFR. Methods: Participants received either dose escalation of FA‐SLIT or placebo over a six month period. Oral food challenge was performed at the beginning and end of the study, along with clinical examinations and collection of skin surface bacterial cytology and blood. Peripheral blood mononuclear cells were stimulated with the culprit food antigen. ELISA methods were used to quantify Interleukin (IL)‐10, IFN‐γ, IL‐4 and IL‐17A in the supernatant of stimulated cells. Results: IL‐10 and IFN‐γ levels were significantly increased at the end of the study in the treatment group (T), compared with the placebo group (P), whereas no changes were found in IL‐4 levels. IL‐17A levels were decreased in both groups (but more profoundly in T). Bacterial scores on the skin were positively correlated with IL‐17A and inversely correlated with IL‐10 concentrations. Interleukins were not correlated with clinical scores. Conclusion and clinical importance: FA‐SLIT may modulate the allergic response toward Th1 and Treg cell phenotypes, and induction of tolerance in dogs with AFR. Therefore, FA‐SLIT may be a tool to desensitize dogs with AFR. However, more data on a larger number of cases and a broader panel of cytokines are needed to corroborate these findings, and to elucidate the mechanism of action for responses to FA‐SLIT by dogs with AFR. Abstract : Background – Food allergen‐specific sublingual immunotherapy (FA‐SLIT) is considered to be a novel, safe and effective approach in dogs with adverse food reactions (AFR).Hypothesis/Objectives – To investigate changes in key cytokines associated with FA‐SLIT.Conclusion and clinical importance – FA‐SLIT may modulate the allergic response toward Th1 and Treg cell phenotypes and induction of tolerance in dogs with AFR. Therefore, FA‐SLIT may be a tool to desensitize dogs with AFR. However, more data on a larger number of cases and a broader panel of cytokines are needed to corroborate these findings, and to elucidate the mechanism of action for responses to FA‐SLIT by dogs with AFR.